Exploring the organisational structure of networks for exercise oncology provision: a social network analysis of OnkoAktiv - Voland, Annelie; Köppel, Maximilian; Peters, Stefan; Wiskemann, Joachim; Wäsche, Hagen (BMC health services research, 2023)
Structured exercise programs provide considerable health benefits for cancer patients. Therefore, various OnkoAktiv (OA) networks were established in Germany with the aim to connect cancer patients with certified exercise programs. However, knowledge about the integration of exercise networks into cancer care systems and conditions of interorganisational collaboration is lacking. The aim of this work was to analyse the OA networks to guide further network development and implementation work.